The Integration of the Traditional Game Engklek in Stimulating Literacy Skills in Children Aged 5–6 Years - Mufidah, Faizatul; Samawi, Ahmad; Mudiono, Alif; Harry, Musleh (Jurnal Pendidikan Islam, 2025)
Literacy is a fundamental aspect of early childhood development, serving as a foundation for future educational stages. However, challenges in teaching literacy often arise due to unengaging methods that are not aligned with children’s developmental stages. This study aims to explore how the integration of the traditional Indonesian game Engklek can serve as a medium to stimulate literacy among children aged 5–6 years. A qualitative research method with a case study approach was employed, involving participatory observation and in-depth interviews with teachers and children aged 5–6 years. The findings indicate that Engklek increases children’s interest and motivation in learning to recognize letters and words through active and enjoyable experiences. Children more easily recall letter shapes and vocabulary through the physical activities embedded in the game. Additionally, social interaction during the gameplay supports the development of communication skills and self-confidence. This study concludes that the traditional game Engklek can be adapted as an effective method for stimulating early childhood literacy, offering a creative and culturally relevant alternative to conventional learning methods.